Orthodontics as a therapeutic option for temporomandibular disorders: A systematic review - Machado, Eduardo; Machado, Patricia; Grehs, Renésio Armindo [UNESP]; Cunali, Paulo Afonso (FapUNIFESP (SciELO), 2012)
Objective: Orthodontics as an option for treatment and prevention of Temporomandibular Disorders (TMD) is a topic that has generated discussion over time. While an occlusion current defends Orthodontics as an alternative to treatment, another current defends more conservative and reversible treatments. The objective of this study, through a systematic literature review, was to analyze the relationship between Orthodontics and TMD, checking the effects of orthodontic therapy in treatment and prevention of TMD. Methods: Survey in research bases: MEDLINE, Cochrane, EMBASE, Pubmed, Lilacs and BBO, between the years of 1966 and May 2009, with focus in randomized clinical trials, non-randomized prospective longitudinal studies, systematic reviews and meta-analysis was performed. Results: After application of the inclusion criteria 11 articles were selected, 9 which were non-randomized prospective longitudinal studies, 1 randomized clinical trial and 1 systematic review. Conclusions: According to the literature, there is a lack of specific studies that evaluated Orthodontics as an option for treatment and prevention of TMD. Thus the data conclude that there is no significant scientific evidences that orthodontic treatment treats or prevents TMD. © 2012 Dental Press Journal of Orthodontics.
Keywords: Craniomandibular disorders; Dental occlusion; Orthodontics; Temporomandibular joint; Temporomandibular joint disorders; Temporomandibular joint dysfunction syndrome